Analisis dan Desain Modifikasi Jembatan Rangka Busur Baja dengan Fluid Viscous Damper Menggunakan SAP2000 - Akbari, Muhamad Fauzan; Saputra, Yohanes Hadi; Alghiffary, Rizqi; Velantika, Griselda Junianda; Eka Putri, Karina Melawati; Widowati, Elok Dewi (Jurnal Proyek Teknik Sipil, 2025)
ABSTRACT The bridge design modification presented in this study focuses on implementing a steel arch truss system combined with Fluid Viscous Dampers (FVDs) to improve structural efficiency and seismic resilience. The steel arch truss enables a longer main span with fewer intermediate supports, offering construction advantages, enhanced stability, and improved aesthetics. Additionally, the integration of FVDs aims to reduce structural displacements during seismic events, thereby minimizing potential post-earthquake damage.The object of this study is referred to as Bridge XYZ, assumed to be one of the key bridges in Gresik Regency, serving as a vital connection between Gresik and Lamongan. This bridge plays a strategic role in supporting mobility and logistics distribution in the region, making structural optimization and seismic mitigation essential. The research methodology includes data collection and literature review, followed by the structural redesign process. Structural modeling and analysis were conducted using SAP2000 software, adhering to Indonesian bridge and seismic design standards. The primary objective is to develop a single-span bridge configuration using steel orthotropic decks for a lighter superstructure and to evaluate the effectiveness of FVDs in reducing seismic-induced displacements. The analysis results show that the redesigned bridge utilizes BJ55 steel orthotropic deck plates with T-profile ribs, cross girders with WF profiles, tie beams with box girders, and Macalloy suspension cables. The application of FVDs successfully reduced seismic displacement by 3% to 45%, demonstrating their effectiveness in enhancing the bridge’s structural resilience.KEYWORDS Fluid Viscous Damper; SAP2000; Steel Arch Truss.